Balance of Payments Anti-Crises - Yan, Isabel (IMF Working Papers; Working Paper, 2009)
Several emerging economies have, until recently, experienced large government surpluses and accelerating foreign exchange reserve accumulation. This has been accompanied by economic booms, exchange rate appreciations and in some cases increases in domestic inflation. We show that one way to understand these episodes is as manifestations of balance of payments anti-crises, as reflecting the perception that the government intends to discontinue its accumulation of reserves in the near future. The end-phase of such crises is characterized by nominal interest rates approaching their zero lower bound in accelerating fashion and, if the government targets CPI inflation, by fast increasing domestic inflation.